Cocrystals of Li+ encapsulated fullerenes and Tb(iii) double-decker single molecule magnet in a quasi-kagome lattice. Issue 84 (23rd September 2020) - Iwami, Hikaru; Xing, Junfei; Nakanishi, Ryo; Horii, Yoji; Katoh, Keiichi; Breedlove, Brian K.; Kawachi, Kazuhiko; Kasama, Yasuhiko; Kwon, Eunsang; Yamashita, Masahiro
Abstract : Cocrystallization of a lithium ion encapsulated fullerene with a terbium(iii ) phthalocyaninato porphyrinato double-decker single-molecule magnet results in a quasi-kagome lattice packing showing ferromagnetic spin arrangement. Abstract : Cocrystallization of a lithium ion encapsulated fullerene Li + @C60 with a terbium(iii ) phthalocyaninato porphyrinato double-decker single-molecule magnet [Tb(Pc)(OEP)] is reported. The cocrystal, containing PF6 − as a counter anion, packs in a quasi-kagome lattice, which leads to intermolecular ferromagnetic interactions as well as the modulation of the single-molecule magnet (SMM) properties.